Application of Intermediate-Wave Infrared Drying in Preparation of Mushroom Chewing Tablets - Wang, L.; Zhang, M.; Fang, Zhongxiang; Xu, B. (Taylor & Francis, 2014)
Two drying methods, namely intermediate-wave infrared drying (IWIR) and hot-air drying (HA), were compared in preparation of mushroom chewing tablets (MCT). It was observed that IWIR enhanced the drying rate and shortened the time required for MCT. IWIR technology was better than HA in preserving thermalsensitive materials by thermo gravimetric analysis. In addition, IWIR had a significant effect on the flavor of the samples, which would be used for retaining flavor ingredients and be conducive to the processing of the product. The results indicated that IWIR may have the potential to be developed as a new drying process in the food industry.